ENERGY EVALUATION OF THE POWER SUPPLY OF A THREE-PHASE MOTOR IN A SINGLE-PHASE NETWORK USING CAPACITORS (Journal of Industrial and Mechanical Engineering, 2020)
In this experimental research, a statistical comparison is made of measurements of active power, reactive power, power factor, current imbalance of a three-phase motor by two connection methods, feeding thethree-phase motor connected to a three-phase network and Connected to a single-phase network to demonstrate if there are significant differences, the measurements taken by the Energy Quality Analyzer will provide the parameters of the quality of the electrical energy in the two cases of motor operation.
Keywords: Energy Quality Analyzer; three phase network; single phase network; imbalance; capacitor